Correlation between interalar width and intercommisural width toward mesiodistal width of upper central incisor on Buton tribe - Bahruddin Thalib; Lenny Alvionita (DiscoverSys Inc., 2016)
Various types of facial anatomy landmarks which must have an appropriate proportion to the size of the tooth is interalar width, intercommisural width, interpupillary width, intercanthal width, and byzigomatic width. Different facial anatomy landmark is influenced by age, gender, region of residence and origin of his tribe. Tribe or race is a race classification based on physical characteristics, such as face shape, hair, and skin color. The tribes who originally inhabited the Southeast Sulawesi namely Tolaki tribe, Muna tribe and Buton tribe. All three of these tribes have typical anatomical landmarks.The objective of this study was to evaluate the correlation between interalar width and intercommisural width against mesiodistal incisivus centralis width in a group of Buton tribe. Ninety five Buton tribe subjects aged 17-25 were selected. The interalar width, intercommisural width, and mesiodistal incisor centralis teeth were measured using caliper about three times for accuracy and precision. The degree of correlation between interalar width against mesiodistal incisor centralis maxilla width was 0.278 and 0.325 in Buton tribe and females (p<0.05) and 0.168 in males (p>0.05). the degree of correlation etweenintercommisural width against mesiodistal incisor centralis maxilla width was 0.310 and 0.420 in Buton tribe and females (p<0.05) and 0.125 in males (p>0.05). The degree of correlation between interalar width against intercommisural width was 0.565,0.585, and 0.455 in Buton tribe , males and females (p<0.05). In conclusion, there is a significant correlation between interalar width and incommisural width against mesiodistal incisor centralis maxilla width in a group of Buton tribe. Interalar width and intercommisural width directly proportional to mesiodistal incisor centralis maxilla width in both of gender of Buton tribe.